A new species of Phyllanthus (Phyllanthaceae) hiding in the shades in an urban Atlantic Forest in Rio de Janeiro State, Brazil - Mendes, Jone Clebson Ribeiro; Braga, João Marcelo Alvarenga; Fraga, Claudio Nicoletti De; Tomazello-Filho, Mario; Orlandini, Priscila; Athiê-Souza, Sarah Maria (Phytotaxa, 2024)
A new and critically endangered species of Phyllanthus, endemic to the Parque Nacional da Tijuca in Rio de Janeiro State, Brazil, is described and illustrated here. Phyllanthus celatus is placed in Phyllanthus subgenus Phyllanthus section Phyllanthus subsection Phyllanthus. Morphologically it resembles P. augustinii, P. lobatus and P. niruri, but differs mainly by presenting reddish primary, secondary and intersecondary veins on the abaxial surface (vs absent in both species), and 5-lobed pistillate disc (vs entire only in P. augustinii and P. niruri). Of these, only P. lobatus has a lobed disc, but it differs in pistillate sepals light green (vs whitish or slightly pinkish), deeply 5-lobed pistillate glandular disc (vs 3–5-lobed), styles erect (vs curved), and geographic distribution restricted to the Southeast (vs South). The systematic position of this species and its morphological relationships with allies are discussed and field photographs, illustrations, a distribution map, preliminary conservation status, and taxonomic notes are provided.